A digital communication plan for Quiksilver, Portugal - Uttrup, Emilie Bekhoj (2018)
Quiksilver is a worldwide company that came to Portugal for the first time 30 years ago on a license, which was brought back to the Quiksilver group in 2011 before the opening of their own flagship store in Ericeira, Portugal. Only the brand DC shoes is remaining as a distributor on the Portuguese market. Since the creation of the store in Ericeira, Quiksilver has been the center for many sports events, parties and concerts. The store remains the 3rd largest Quiksilver store in the world. Despite this, Quiksilver, Portugal faces challenges within sales, communication and marketing. Quiksilver operates in a high competitive environment, with a lot of direct and indirect competitors, meaning that it is very important that Quiksilver is innovative and able to adapt to all the new trends within the market. During the last two decades the internet has grown rapidly and companies have had to adapt their marketing communication plan to include all the new opportunities the new digital technology have brought with it. This research is therefore aiming to decide how Quiksilver, Portugal can improve their digital marketing communication plan in order to generate more sales, receive more publicity and gain consumer engagement. The main focus will be on Quiksilver´s use of digital media and how it can be improved to achieve the objectives.